Detection of STH Worm Eggs on Students' Nails at UPT SPF SDN 258 Sakui-Kui Elementary School - Islawati Islawati; Asdinar Asdinar; Asriyani Ridwan (Jurnal Pengabdian Masyarakat, 2024)
Helminth infections remain one of the most common parasitic diseases affecting children, particularly at the primary school level, where awareness of personal hygiene is generally low. One of the main transmission routes of this infection is through unclean hands. This community service activity at UPT SPF SDN 258 Sakui-Kui aimed to enhance students' understanding of the importance of personal hygiene, specifically by educating them on proper handwashing techniques based on WHO standards. The tools used in this activity included a whiteboard, nail clippers, a camera, a microscope, test tubes, glass slides, cover slips, stirring rods, basins, beakers, petri dishes, test tube racks, and stationery, while the materials used included nail samples from students, water, and salt. The evaluation results indicated that this activity effectively increased students' understanding of personal sanitation by up to 90%, as evidenced by observational evaluations of direct practice. Additionally, students gained knowledge that helminth eggs adhering to nails could cause infections if ingested with food. This educational initiative had a significant impact on shaping students’ personal hygiene behavior, potentially reducing the risk of parasitic infections within the school environment.